Wölfflin's Grundbegriffe as a psychological palimpsest? Review of Heinrich Wölfflin, Principles of Art History. One Hundredth Anniversary Edition, translated by Jonathan Blower and edited by Evonne Levy and Tristan Weddigen, ix + 357 pp. Issue 13 (December 2015) - Witte, Arnold
No abstract available